1973
DOI: 10.1111/j.1600-0722.1973.tb00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil chemotactic substances in different fractions of soluble dental plaque material

Abstract: abstract— Extracts of 4‐day‐old dental plaque were fractionated on Sephadex® columns (G‐10; G‐25; G‐200). Five fractions were selected from the protein and conductivity peaks obtained in chromatograms. The chemotactic activity elaborated by the fractions was tested in the Boyden's in vitro model system. The permeability altering capacity of the plaque fractions was tested in vivo in a wound chamber. The results from the in vitro experiments demonstrated that all fractions were chemotactic for rabbit neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…This observation corroborates results previously reported by e.g. Tempel et al (1970), Miller, Umana & Folke (1971, Lindhe & Hellden (1972), Hellden, Ericsson & Lindhe (1973), Kraal & Loesche (1974) describing that material obtained from dental plaque or from Actinomyces and Streptococcus strains was consistently active for neutrophil chemotaxis when tested both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation corroborates results previously reported by e.g. Tempel et al (1970), Miller, Umana & Folke (1971, Lindhe & Hellden (1972), Hellden, Ericsson & Lindhe (1973), Kraal & Loesche (1974) describing that material obtained from dental plaque or from Actinomyces and Streptococcus strains was consistently active for neutrophil chemotaxis when tested both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…Tempel et al (1970) isolated a small molecular weight peptide from pure cultures of a hamster strain of A. viscosus with chemotactic activity. Similar properties could be demonstrated directly in supernatants of human dental plaque with peak activities in small molecular weight fractions (Hellden, Ericsson & Lindhe 1973). Chemotactic factors have not been sought in cultures of Gram-negative plaque bacteria.…”
Section: Discussionmentioning
confidence: 86%
“…When different fractions were tested regarding their chemotactic activity it was found that all the plaque fractions tested attracted mononuclear leukocytes. The findings were thus in line with earlier published data concerning the capacity of dental plaque to attract neutrophilic Ieukoc34es (Tenapel et al 1970, Miller et al 1971, Lindhe & Helldeo 1972, Hellden, Ericson & Lindhe 1973. However, the molecular size of the plaqne fraction that induced the major part of the inonoc3fte chemotactic activity was larger than that of the corresponding neutrophil chemotactic factor .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, plaque accumulation will be inhibited by chiorhexidine, and this should greatly increase the tendency toward healing. In fact, the application of plaque extract led to a more severe inflammatory reaction within granulation tissue when compared to chlorhexidine (Lindhe & Hellden 1972, Hellden et al 1973. The positive influence of plaque inhibition on wound healing has also been demonstrated by Hamp et al, (1975) in his histoiogically verified studies of the epithelial attachment in dogs, though these results are representative of only the especially contaminated gingival area.…”
Section: Discussionmentioning
confidence: 91%